Psychological implications in children's drawings in nurseries - نضال كاظم مطر (College of Education for Women, 2019)
Education is one of the most important topics that researcher educator and educational society as a whole operated in the latter half of the twentieth century, which won the reflection and study many of officials in the educational cocked in the global regionally and took educational systems around the world interested in the dimensions of this aspect and planning to achieve the principle and characteristics in order to be in concerned with the in dividual to provide an opportunity for education and training.Experiments have been taken from this type of education in the world, including the developing world snd Islam was still taken on taking science life for the rest of the human sons and on this basis, we find that studies and research took strong principle to keep the individual and human ignorance and illiteracy to prosecute evolution and techniques imposed on it today and in the future.Many Research studies have focused on studying for education in terms of policy and programmed method and it's concept and its fields and constraints for students in community ,schools and kindergartens exclusively. It also contributed to education in broad cast artistic culture among children. As a work very much beneficial. and adopted the duty on it .Nabil and commitment toward society and human .the value and properties .Fiqimtart education and Swabath , Kamann an in the search do not complain about the complexity and concavity. Nor Bghos in details ?And a steady drumbeat of various theories or condractories .a shelters also divers and inclusive for all all psychological revelation received by the mind of a child the portrayal in the drawings are often expressed in words as well as drawings in deliver the idea that recipient cannot be embodied by his drawings of simple and expressive colour.. This is taken into consideration in this research as well as it covers many fields and benefits researchers in this field. Therefore, the current research is trying to take a closer look at the psychological implications in children's drawings in the nursery. The first chapter came defined the importance of research and the need for it as well as the research problem after placing the following objectives: Research Objectives The research aims to identify .. 1.identify the children's drawings in kindergartenageof4_6years. 2. To identify the topics that kids resolve and draw most important things to focus in their drawings. 3.psychological effect and impression left by the societies in children's thinking through expression with graphics in the nursery. 4.psychological revelations through children's drawingsandby themes that were given to them. Border research Is determined by the current search 1.objective limits: includes general philosophy of children's drawings from the face of the scientific review. 2.Spatial Order: include kindergarten eligibility birds of paradise in Zafaranyia /Baghdad area. 3.temporal limits :the academic year2013-2014 The Second chapter, including previous st and philosophical framework and monetary research. While chap III procedures. Chapter IV contains the conclusion and recommendation proposals of Arab and foreign sources and result relied upon by the current research as well as summary of the Arabic language and a summary in English.